Sufficient Dilated LMI Conditions for H∞ Static Output Feedback Robust Stabilization of Linear Continuous-Time Systems. (7th March 2012) - Dabboussi, Kamel; Zrida, Jalel
Abstract : New sufficient dilated linear matrix inequality (LMI) conditions for theH ∞ static output feedback control problem of linear continuous-time systems with no uncertainty are proposed. The used technique easily and successfully extends to systems with polytopic uncertainties, by means of parameter-dependent Lyapunov functions (PDLFs). In order to reduce the conservatism existing in early standard LMI methods, auxiliary slack variables with even more relaxed structure are employed. It is shown that these slack variables provide additional flexibility to the solution. It is also shown, in this paper, that the proposed dilated LMI-based conditions always encompass the standard LMI-based ones. Numerical examples are given to illustrate the merits of the proposed method.